2019
DOI: 10.1088/1757-899x/543/1/012026
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nickel – hydroxyapatite by electrochemical method

Abstract: The electrochemical method in two chambers with the bipolar membrane has been used to produce the nickel – hydroxyapatite particle. Hydroxyapatite is used as the supported catalyst for nickel catalyst. In this work, in-situ electrochemical synthesis in two chambers with bipolar membrane has been used in the formation of nickel-hydroxyapatite. A simple electrolysis cell from acrylic was used. The anode and the cathode were set parallel with a distance of 3 cm and immersed in the solution at a depth of 2 cm. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…On the other hand, the highest crystallinity was observed for sample 1.5 (82.8%), whereas the crystallinity degree of sample 1.0 was 75.1%. On this basis, it can be concluded that the method produces phase-pure and crystalline [55,56].…”
Section: X-ray Diffraction Analysismentioning
confidence: 87%
“…On the other hand, the highest crystallinity was observed for sample 1.5 (82.8%), whereas the crystallinity degree of sample 1.0 was 75.1%. On this basis, it can be concluded that the method produces phase-pure and crystalline [55,56].…”
Section: X-ray Diffraction Analysismentioning
confidence: 87%
“…In this work, Ni-B catalyst is used as the catalyst and hydroxyapatite as the catalyst support. In previous studies, Ni/hydroxyapatite particles were successfully synthesized electrochemically [11]. The use of bipolar membranes in electrochemical synthesis strongly supported the electrolysis [12,13,14].…”
Section: Introductionmentioning
confidence: 94%